Biofilm Quantification on Nasolacrimal Silastic Stents After Dacryocystorhinostomy. Issue 5 (September 2015) - Murphy, Jae; Ali, Mohammed Javed; Psaltis, Alkis James
<x xml:space="preserve">Abstract</x> Purpose: Biofilms are now recognized as potential factors in the pathogenesis of chronic inflammatory and infective diseases. The aim of this study was to examine the presence of biofilms and quantify their biomass on silastic nasolacrimal duct stents inserted after dacryocystorhinostomy (DCR). Methods: A prospective study was performed on a series of patients undergoing DCR with O'Donoghue stent insertion. After removal, the stents were subjected to biofilm analysis using standard protocols of confocal laser scanning microscopy (CLSM) and scanning electron microscopy. These stents were compared against negative controls and positive in vitro ones established using Staphylococcus aureus strain ATCC 25923. Biofilm quantification was performed using the COMSTAT2 software and the total biofilm biomass was calculated. Results: A total of nine consecutive patient samples were included in this prospective study. None of the patients had any evidence of postoperative infection. All the stents demonstrated evidence of biofilm formation using both imaging modalities. The presence of various different sized organisms within a common exopolysaccharide matrix on CLSM suggested the existence of polymicrobial communities. The mean biomass of patient samples was 0.9385 μm3/μm2 (range: 0.3901–1.9511 μm3/μm2). Conclusions: This is the first study to report the quantification of biomass on lacrimal stents. The presence of biofilms on lacrimal stents after DCR is a common finding but this need not necessarily translate to postoperative clinical infection.